Produção de tilápias-do-Nilo em sistemas sem renovação de água com Wetlands para tratamento de efluentes - Amorim, Rafael Vieira [UNESP] (2014)
The main objectives of master’s dissertation were: (Chapter II) to evaluate the production and the quality of water from the cultivation of Nile tilapia (Oreochromis niloticus) in systems with substrates and without the reconditioning of water; (Chapter III) evaluate the efficiency of wetlands constructed and stocked with two species of floating aquatic macrophytes (Eichhornia crassipes and Pistia stratiotes) in the treatment of harvest wasterwater from final growth tanks which contained tilapia.The result of Chapter II shows that the use of cultivation systems without the reconditioning of water and with artificial substrates in tilapia production can present good yields, accumulating some nutrients in water from the cultivation, however this system was shown to be efficient in the absorption of inorganic nitrogen and orthophosphate during the cultivation, probably due to the presence of substrate. In Chapter III, wetlands constructed and stocked with E. crassipes and P. stratiotes, with a hydraulic retention time of 336 hours, presented efficiency in the treatment of harvest effluent from the water in the final growth tanks which contained Nile tilapia; with the removal of nutrients occurring in the first hours of treatment. But the wetlands constructed with E. crassipes were more efficient in the removal of concentrations of total phosphorus, being more feasible for wastewater treatment which has high concentrations of total phosphorus